SII@EDU social innovation initiatives: Artventure.19 / Roslaili Anuar ... [et al.] - Anuar, Roslaili; Othman, Noor Farhani; Maaruf, Siti Zuraida; Universiti Teknologi MARA, Galeri Seni Tuanku Nur Zahirah (GESTURZ) (Galeri Seni Tuanku Nur Zahirah (GESTURZ), Universiti Teknologi MARA in collaboration with Faculty of Education (EDU), Universiti Teknologi MARA, Shah Alam, 2020)
This event was the second series of the Artventure programme organised to expose preschool children to new experience outside the classroom. This programme was a collaboration with GESTURZ and participated by preschool students from Sekolah Kebangsaan Raja Muda, Shah Alam.